KAJIAN JALUR PEDESTRIAN PADA JALAN CIHAMPELAS BANDUNG - , HENDARWAN; , Ir. Ikaputra, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study has a background of concerns about the condition of the cities in Indonesia, which currently has a tendency to accommodate modes of transport \"non-pedestrian\", but walking is the most basic mode of transport and main informal and uncomplicated for a person. One of these was Cihampelas Street Bandung. Which is a commercial area, the left and right of the road filled with \"factory outlet\". The pedestrians are not facilitated with good facilities, whereas the majority of the visit did walk to the achievement of one place to another. Pedestrian way is disconnected, covered parking and street vendors, damaged, street furniture which is very less, all of which make the pedestrians canât be facilitated by a pedestrian way, so it is necessary to study Cihampelas Street Pedestrian Way that will be able to provide comfort and security for pedestrians. This research method has a method with the existing data in the field is then processed by way of drawn and analyzed to determine the physical setting of the pedestrian way and assessed with aspects Connectivity, Convenience, Attractivness, Safety, Security to determine the quality of the pedestrian way. Having in mind the quality of the pedestrian way, will be known aspects that need to be improved and recommendations should be given so as to improve the comfort of the pedestrian way on the road Cihampelas Bandung.